Reciprocal Crosstalk between Dendritic Cells and Natural Killer T Cells: Mechanisms and Therapeutic Potential - Keller, Christian W.; Freigang, Stefan; Lünemann, Jan D. (Frontiers in Immunology, 2017)
Natural killer T cells carrying a highly conserved, semi-invariant T cell receptor (iNKT cells) are a conserved subset of unconventional T lymphocytes that recognize glycolipids presented by CD1d molecules. Although CD1d is expressed on a variety of hematopoietic and non-hematopoietic cells, dendritic cells (DCs) are key presenters of glycolipid antigen in vivo. When stimulated through their T cell receptor, iNKT cells rapidly secrete copious amounts of cytokines and induce maturation of DCs, thereby facilitating coordinated stimulation of innate and adaptive immune responses. The bidirectional crosstalk between DCs and iNKT cells determines the functional outcome of iNKT cell-targeted responses and iNKT cell agonists are used and currently being evaluated as adjuvants to enhance the efficacy of anti-tumor immunotherapy. This review illustrates mechanistic underpinnings of reciprocal DCs and iNKT cell interactions and discusses how those can be harnessed for cancer therapy.